2023
DOI: 10.1111/ejh.13919
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of calcium channel blockers in preventing cardiac siderosis in thalassemia patients: An updated meta‐analysis with trial sequential analysis

Abstract: Objectives Iron overload in patients with thalassemia represents a serious complication by affecting numerous organ systems. This meta‐analysis aims to establish an evidence regarding the effect of amlodipine on cardiac iron overload in thalassemia patients. Methods We searched PubMed, Scopus, Web of Science, Cochrane Central, and EMBASE for all relevant randomized controlled trials (RCTs). The primary outcomes were cardiac T2* and myocardial iron concentration (MIC). Secondary outcomes were liver iron concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Rash, Renal disorders, Gastrointestinal problems [118] There are currently many other iron chelators that show great promise towards mitigating iron overload, like Deferitazole and SP-420 [119,120]. Amlodipine, a calcium channel blocker, has been reported to be efficient in decreasing myocardial iron concentration and significantly elevating cardiac T2*, which indicates its role for the treatment of cardiac iron overload [121]. Furthermore, a recently discovered novel erythroid maturation agent, luspatercept, has been reported to lower the serum ferritin levels in adult β-thalassemic patients, as well as significantly reduce the number of blood transfusions (>33%) in TDT patients (BELIEVE trial) [122].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Rash, Renal disorders, Gastrointestinal problems [118] There are currently many other iron chelators that show great promise towards mitigating iron overload, like Deferitazole and SP-420 [119,120]. Amlodipine, a calcium channel blocker, has been reported to be efficient in decreasing myocardial iron concentration and significantly elevating cardiac T2*, which indicates its role for the treatment of cardiac iron overload [121]. Furthermore, a recently discovered novel erythroid maturation agent, luspatercept, has been reported to lower the serum ferritin levels in adult β-thalassemic patients, as well as significantly reduce the number of blood transfusions (>33%) in TDT patients (BELIEVE trial) [122].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A meta-analysis [19] on three randomized controlled trials (n = 130 patients) unveiled a non-significant difference in serum ferritin between amlodipine and control groups, with a weighted mean difference (WMD) of −0.16, and 95% confidence interval (CI) −0.51 to 0.19. Moreover, a recent systematic review found that amlodipine can significantly improve cardiac T2-weighted magnetic resonance imaging (MRI T2*) and myocardial iron concentration (MIC) and even reduce the incidence of cardiomyopathy-related iron overload in thalassemia patients without significant side effects [20]. The values of Hedges' g for cardiac MRI T2* and MIC were 0.36, 95% CI 0.10-0.62 and −0.82, 95% CI −1.40 to −0.24, respectively.…”
Section: Introductionmentioning
confidence: 99%